Large-Scale Dryland Cropping Systems - A. Schlegel; L. Haag (Kansas Agricultural Experiment Station Research Reports, 2017)
This study was conducted from 2008 to 2016 at the Kansas State University Southwest Research-Extension Center near Tribune, KS. The purpose of the study was to identify whether more intensive cropping systems can enhance and stabilize production in rainfed cropping systems to optimize economic crop production, more efficiently capture and utilize scarce precipitation, and maintain or enhance soil resources and environmental quality. The crop rotations evaluated were continuous grain sorghum (SS), wheat-fallow (WF), wheat-corn-fallow (WCF), wheat-sorghum-fallow (WSF), wheat-corn-sorghum-fallow (WCSF), and wheat-sorghum-corn-fallow (WSCF). All rotations were grown using no-tillage practices except for WF, which was grown using reduced-tillage. The efficiency of precipitation capture was not greater with more intensive rotations. Length of rotation did not affect wheat yields. Corn yields were about 55% and grain sorghum yields about 70% greater when following wheat than when following corn or grain sorghum. Grain sorghum yields were about 60% greater than corn in similar rotations.
Keywords: crop rotations; grain sorghum; corn; wheat; no-till; reduced tillage